2008
DOI: 10.1111/j.1600-079x.2007.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and ischemia–reperfusion injury of the brain

Abstract: :  This review summarizes the reports that have documented the neuroprotective effects of melatonin against ischemia/reperfusion brain injury. The studies were carried out on several species, using models of acute focal or global cerebral ischemia under different treatment schedules. The neuroprotective actions of melatonin were observed during critical evolving periods for cell processes of immediate or delayed neuronal death and brain injury, early after the ischemia/reperfusion episode. Late neural phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 84 publications
(112 reference statements)
1
59
1
Order By: Relevance
“…While the extent of volumetric brain tissue loss is a reliable finding, the neuronal density measurements could be an overestimation of neuronal viability, since our methods could not differentiate between living and dead neurons, and this should be addressed in future studies. The difference between the findings of our study and those of previous reports, however, may be related to the dual actions of melatonin (and its metabolites), as both a potent antioxidant and a free-radical scavenger (Cervantes et al, 2008;Peyrot and Ducrocq, 2008;Tan et al, 2007), suggesting broader reductions of oxidative stress and subsequently less cell and tissue damage with melatonin treatment. This possibility is further corroborated by the fact that we saw a significant reversal of oxidative stress, which has not been previously shown after striatal collagenase-induced ICH (Peeling et al, 2001a(Peeling et al, , 1998.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…While the extent of volumetric brain tissue loss is a reliable finding, the neuronal density measurements could be an overestimation of neuronal viability, since our methods could not differentiate between living and dead neurons, and this should be addressed in future studies. The difference between the findings of our study and those of previous reports, however, may be related to the dual actions of melatonin (and its metabolites), as both a potent antioxidant and a free-radical scavenger (Cervantes et al, 2008;Peyrot and Ducrocq, 2008;Tan et al, 2007), suggesting broader reductions of oxidative stress and subsequently less cell and tissue damage with melatonin treatment. This possibility is further corroborated by the fact that we saw a significant reversal of oxidative stress, which has not been previously shown after striatal collagenase-induced ICH (Peeling et al, 2001a(Peeling et al, , 1998.…”
contrasting
confidence: 99%
“…Melatonin (5-methoxy-N-acetyl-tryptamine) and its metabolites are potent antioxidants and free-radical scavengers (Cervantes et al, 2008;Peyrot and Ducrocq, 2008;Tan et al, 2007). Regarding erythrocytes, melatonin has been shown to inhibit free radical-associated red blood cell lysis (Tesoriere et al, 1999) and hemoglobin degradation (Tesoriere et al, 2001).…”
mentioning
confidence: 99%
“…This effect, which is evidenced by reduced infarct volume, necrotic neuronal death, together with diminished neurologic deficits and increased number of surviving neurons, can shield brain function [90]. The beneficial properties of melatonin in countering stroke injury can be manifested even if administered 24 h after an ischemic lesion [91].…”
Section: The Potential For Melatonin Treatment Of Specific Neurologicmentioning
confidence: 99%
“…The underlying mechanisms have been extensively studied and the outstanding ability of melatonin to reduce oxidative stress is most emphasized (Pei et al 2002b). In addition to its antioxidant actions, research has also revealed that melatonin exerts its protective effects by improving mitochondrial function and interfering with both proapoptotic cell signaling and synthesis of inflammatory cytokines (Cervantes et al 2008). Furthermore, recent evidence demonstrates that the activation of MT2 melatonin receptor in the hippocampal CA1 region may be involved in the neuroprotective effect of melatonin after ischemic injury (Lee et al 2010).…”
Section: Neuroprotective Effects Of Melatonin On Ischemic Injurymentioning
confidence: 99%